Illuminating, through immunohistochemistry, the link between SARS‐CoV‐2 and pernio (chilblains). (1st September 2020) - Wetter, D.A.
Abstract : Linked Article: Colmenero et al. Br J Dermatol 2020; 183 :729–737 .